The philosophy of language in Gadādhara's Śaktivāda - Ganeri, J; Ganeri, Jonardon (1993)
﻿This thesis is a study of the theory of meaning developed by the seventeenth century Indian Naiyāyika philosopher Gadādhara Bhaṭṭācārya. It has four chapters and an appendix. In chapter 1, I highlight some of the problems about meaning and reference thematised by the Indian philosophical tradition during its 'classical' period (third century B.C.E. to seventh century C.E). The work of the earliest grammarians proved very influential We tend to associate the name of the grammarian Vyddi with the origins of the study of singular reference in classical India, and I look at his theory, the problems it faced, and the innovations of early Nyāya, Mimāṃsā and grammarian authors. In the second chapter, I discuss Gadādhara's analysis of the semantics of nominal stems, his construction of a 'two-component' theory of meaning, and his criticisms of the work of earlier Navya-Naiyāyikas, especially Vardhamāna and Raghunātha. The main theme of this debate concerns the failure of a realist or referential theory of meaning to serve as a complete theory of meaning, one which recognises both the intensional and the context-invariant elements in the meaning of nominal expressions. The third chapter deals with Gadādhara's theory of anaphoric pronouns. I argue in particular that Gadādhara's use of a two-component meaning theory enables him to construct a theory ofpronouns which significantly improves on the proposals of earlier Navya-Nyāya authors. In the fourth chapter, I discuss the epistemological dimension to the Nyāya conception of language; the Nyāya doctrine that linguistic competence consists in the knowledge of a compositional meaning theory; the role of convention in the Nyāya theory, and their thesis that conventions are grounded in the authority of the name-giver. I have added an appendix in which I examine the technical language by means of which Gadādhara is able to give his arguments great precision. I show that this language can be translated into a certain fragment of quantified first-order predicate logic.